One-year assessment of the CHAOS two-way coupled atmosphere-ocean wave modelling system over the Mediterranean and Black Seas - VARLAS, GEORGE; SPYROU, CHRISTOS; PAPADOPOULOS, ANASTASIOS; KORRES, GERASIMOS; KATSAFADOS, PETROS (Mediterranean Marine Science, 2020)
It is currently clear that the atmosphere and ocean should be simulated by integrated modelling systems resolving interconnected physical factors that determine the Earth’s energy balance. Waves play a key role in the interfacial interaction between the atmosphere and the ocean, regulating momentum, heat and moisture exchange. This study aims to evaluate the CHAOS two-way coupled atmosphere-ocean wave system (Chemical Hydrological Atmospheric Ocean wave System) over the Mediterranean and Black Seas. The evaluation is performed against in situ and remote sensing data for the period from 1 December 2013 to 1 December 2014. CHAOS includes the Weather Research Forecasting (WRF) model, version 3.8, as atmospheric component and the Wave model (WAM) cycle 4.5.4 as ocean wave component, coupled through the OASIS3-MCT coupler, version 3.0. Two continuous model simulation approaches were followed to assess the impact of atmosphere ocean waves coupling. In the first approach (1-way coupling mode), the ocean wave component uses the winds produced by the atmospheric component, while in the second approach (2-way coupling mode) the atmospheric component additionally uses sea state information estimated by the ocean wave component through wave-dependent Charnock parameter computations. In the 2-way coupling mode, the attenuation of the atmospheric flow has a damping effect on wind-generated waves. The simulations in 2-way coupling mode produce more realistic results yielding statistical improvements. Compared against buoy observations, the 2-way mode reduces the root mean square error (RMSE) 1.2% for wind speed and 6.3% for significant wave height, while against Jason-2 satellite retrievals the reduction is 0.5% and 2.4%, respectively. Additionally, the 2-way coupling mode outperformed the 1-way mode under intense wind and wave conditions during the one-year period considered.